Customer Satisfaction: The Role of Excellent Service Factors at Bale Madukara Purwakarta Public Service Mall - Widiya Avianti; Fitria, Dissy (Bulletin of Management and Business, 2023)
One of the causes of weak public services is the low performance of public services as measured by the criticism given by the public regarding the slow service process. There is an additional factor that contributes to the cause of weak public services, namely that the government in offering this type of public assistance is overly regulated towards formal implementation and responsibility. Quantitative methods were applied for this study by conducting associative field research. Services excellent at the Bale Madukara Public Service Mal (MPP) in Purwakarta is the focus of this associative research. The results of this study indicate that partially the independent variable, namely Service Excellent, affects the dependent variable, namely Customer Satisfaction at the Bale Madukara Purwakarta Public Service Mal (MPP) and simultaneously Services Excellent affects Customer Satisfaction at the Bale Madukara Purwakarta Public Service Mal (MPP). And the most dominant indicator of services excellent that affects customer satisfaction is the "Appearance" indicator. Visitors who come to MPP Bale Madukara Purwakarta are satisfied with the